2020
DOI: 10.3390/ijerph17134695
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Musculature and Hand Grip Strength in Bodybuilders and Martial Artists

Abstract: The functional preference for the upper limb influences the occurrence of bilateral differences in other segments of the human body. The aim of the study is to assess the influence of the applied fighting technique and targeted physical effort on the occurrence of asymmetry in body musculature and isometric strength in bodybuilders and competitors of selected martial arts. Academic athletes practicing judo (J), jiu-jitsu (JJ), and bodybuilding (BB) were examined. The control group (C) consisted of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Regarding gender differences, previous studies have found higher hand grip strength values generally for men [ 38 ] and for tennis [ 39 , 40 ] and badminton players [ 37 ], compared to women. The present study found asymmetric hand grip strength regarding padel, similar to other studies [ 7 ] and sports [ 41 , 42 ]. Lack of post-SC hand grip strength changes coincides with the results obtained for badminton [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding gender differences, previous studies have found higher hand grip strength values generally for men [ 38 ] and for tennis [ 39 , 40 ] and badminton players [ 37 ], compared to women. The present study found asymmetric hand grip strength regarding padel, similar to other studies [ 7 ] and sports [ 41 , 42 ]. Lack of post-SC hand grip strength changes coincides with the results obtained for badminton [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…In sports, the side-to-side discrepancies in body morphology may also depend on the characteristics of the particular discipline that the given sportsmen practice [ 13 ]. An analysis was conducted on the influence of the types of martial art techniques and focused physical effort on the occurrence of asymmetry in body musculature and isometric strength in bodybuilders and in competitors of selected martial arts; its results indicated increased directional asymmetry in judo competitors.…”
Section: Introductionmentioning
confidence: 99%
“…Segmental BIA is performed on upper limbs and lower limbs separately, givingat least in theorythe chance of evaluating segmental muscle mass [20][21][22]. Few previous papers have performed this type of measurements, showing for instance a more marked difference for lower than upper limbs in female volleyball players [21].…”
Section: Discussionmentioning
confidence: 99%
“…These variables are associated with muscle structure in terms of body cell mass (BCM) and ratio between extracellular water and intracellular water (ECW/ICW ratio) [15][16][17]; in addition, IR and PhA have also been related to muscle strength and physical activity [18,19]. Finally, it should be reminded that BIA may be performed on the whole body but also separately on upper limbs and lower limbs (segmental BIA), givingat least in theorythe chance of evaluating appendicular muscle mass [20][21][22].…”
Section: Introductionmentioning
confidence: 99%